(untitled) (Journal of Education and Development, 2022)
On the onset of COVID 19 Pandemic, educational institutions took up either virtual online or blended modes of delivery and learning; as an intervention of solving programmed learning retention, transition and completion concerns among students in institutions of higher learning. In spite of the fact that online learning faces access learning challenges; there seems to be myriad issues with online assessment procedures. Despite this, there is still much debate on whether online assessments, particularly examinations, offer the same academic integrity as the traditional on- campus face to face paper assessment (Paulli and Ferrelli 2020). The purpose of this study was to assess the perceptions of undergraduate students on virtual online versus on-campus teaching- learning mode of delivery and assessment. The study anchored on descriptive survey design. A sample of 200 students across different years of study at the Faculty of Education, Kikuyu Campus, University of Nairobi, were targeted. The study used online google form to collect data. Descriptive statistics were applied in data analysis. Data was presented through tables, percentages and graphs. 140 students participated in the study. 86.1% of the respondents were in learning session and 13.9% were not in session. The most preferred mode of delivery is face to face on campus with 69.7 % responses, Virtual online – 21.8% and both, was 8.5%. The major reason for preference was that there are subjects such as mathematics, Kiswahili and English which require physical classroom student – lecturer real interactions and immediate instructional feedback for quality acquisition of skills, knowledge and values; which is completely lacking in online virtual learning; and that online virtual pedagogy flow is usually interrupted with network issues causing in-consistency in coverage of course content. Blended learning was recommended for courses that require intense practical sessions, while the other courses can take up online mode of pedagogy. Conclusively, there is need for further review of online pedagogical approaches, and curriculum policies in order to have aligned online assessments that consider equity in access to online pedagogy, in line with student socio-economic backgrounds and conducive learning environments. More research is needed for effective online pedagogical alignments.